PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS 2 SD NEGERI 5 KAWAN BANGLI - Putu Bagus Adi Pramana Putra; I Gusti Ngurah Triyana; Made Gautama Jayadiningrat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Augmented Reality (AR) learning media is one of the technology-based educational innovations that has the potential to enhance students' learning interest. Based on preliminary observations conducted at SD Negeri 5 Kawan, some students were found to have low enthusiasm and participation during mathematics learning activities. Therefore, an engaging and interactive learning medium is needed to increase students' interest in learning. The research problems in this study are: (1) Is there any effect of using Augmented Reality (AR) learning media on the mathematics learning interest of second-grade students at SD Negeri 5 Kawan?; and (2) How significant is the difference in learning interest between students who learn using Augmented Reality (AR) media and those who learn through conventional instruction?. This study employed a quantitative approach using an experimental research design. The sample consisted of two groups, namely Class II A as the experimental group and Class II B as the control group, each consisting of 33 students. Data were collected using a learning interest questionnaire. The collected data were analyzed using IBM SPSS Statistics 26 through validity testing, reliability testing, normality testing, homogeneity testing, and hypothesis testing using the Independent Samples t-Test. The results of the study revealed that: (1) the average learning interest score of students in the experimental group was 135.15, which was higher than that of the control group at 106.33; (2) the hypothesis test showed that the calculated t-value (9.811) was greater than the t-table value (1.998), resulting in the rejection of H₀ and acceptance of H₁; and (3) the use of Augmented Reality (AR) learning media had a significant effect on students' mathematics learning interest. Therefore, Augmented Reality (AR) learning media can be considered an effective alternative learning tool to improve mathematics learning interest among elementary school students